KONTRIBUSI KEMAMPUAN KONEKSI, KEMAMPUAN REPRESENTASI, DAN DISPOSISI MATEMATIS TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMA SWASTA DI KABUPATEN MANGGARAI - Mandur, Kanisius; Sadra, I Wayan; Suparta, I Nengah (STKIP Santu Paulus Ruteng, 2016)
Abstract: The Contribution of Connection Ability , Representation Ability and Mathematical Disposition toward the Students’ Mathematics Achievement in Private Senior High Schools in Manggarai Regency.This research examines the contribution of four variables, namely: 1) the contribution of mathematical connection ability toward mathematics achievement through mathematical disposition, 2) the contribution of mathematical representation ability toward mathematics achievement through mathematical disposition, 3) the contribution of mathematical connection and mathematical representation ability toward mathematical disposition simultaneously, and 4) the contribution of the connection ability, representation ability and mathematical disposition toward the students’ mathematics achievement simultaneously. Ex post facto research design was employed which involved the population of the second year students’ of science program at private senior high schools in Manggarai regency in academic year 2012/2013. 230 students were the samples selected by cluster sampling technique. The data of the connection and representation mathematical abilities were gathered by essay test. The data of mathematical disposition were collected by questionnaire, whereas for the students’ mathematics achievement were the students’ first semester scores. The data were analyzed in Path Analysis. The results demonstrate that: 1) the contribution of mathematical connection ability toward students’ mathematics achievement through mathematical disposition is 19,36%, 2) the contribution of mathematical representation ability toward students’ mathematics achievement through mathematical disposition is 14,12%, 3) the contribution of mathematical connection and representation ability toward mathematical disposition is 83,7%, and 4) the contribution of connection ability, representation ability, and mathematical disposition toward students’ mathematics achievement is 81,3%. It can be concluded that connection ability, representation ability, and mathematical disposition contribute significantly to mathematics achievement of grade XI science students of Manggarai directly or indirectly. Key words: contribution, connection ability, representation ability, disposition mathematical, and mathematics achievement Abstrak:Kontribusi Kemampuan Koneksi, Kemampuan Representasi, dan Disposisi Matematis Terhadap prestasi belajar matematika Siswa SMA swasta di Kabupaten Manggarai. Penelitian ini bertujuan untuk mengetahui: (1) kontribusi kemampuan koneksi matematis terhadap prestasi belajar matematika melalui disposisi matematis, (2) kontribusi kemampuan representasi matematis terhadap prestasi belajar matematika melalui disposisi matematis, (3) kontribusi kemampuan koneksi dan kemampuan representasi matematis secara simultan terhadap disposisi matematis, dan (4) kontribusi kemampuan koneksi, kemampuan representasi, dan disposisi matematis secara simultan terhadap prestasi belajar matematika. Penelitian ini merupakan penelitian ex post facto. Populasi penelitian ini adalah siswa kelas XI IPA SMA swasta di Kabupaten Manggarai tahun pelajaran 2012/2013. Pengambilan sampel dilakukan dengan cluster sampling. Jumlah anggota sampel penelitian adalah 230 orang. Data kemampuan koneksi dan kemampuan representasi matematis dikumpulkan dengan tes uraian. Data disposisi matematis dikumpulkan dengan angket. Data prestasi belajar matematika diperoleh dari nilai raport semester satu siswa kelas XI IPA. Data dianalisis dengan menggunakan analisis jalur. Hasil penelitian menunjukkan bahwa: (1) besar kontribusi kemampuan koneksi matematis terhadap prestasi belajar matematika melalui disposisi matematis adalah 19,36%, (2) besar kontribusi kemampuan representasi matematis terhadap prestasi belajar matematika melalui disposisi matematis adalah 14,12%, (3) besar kontribusi kemampuan koneksi dan kemampuan representasi terhadap disposisi matematis adalah 83,7%, dan (4) besar kontribusi kemampuan koneksi, kemampuan representasi, dan disposisi matematis terhadap prestasi belajar adalah 81,3%. Berdasarkan temuan tersebut disimpulkan bahwa kemampuan koneksi, kemampuan representasi, dan disposisi matematis berkontribusi secara signifikan terhadap prestasi belajar matematika siswa kelas XI IPA di Kabupaten Manggarai, baik secara langsung maupun tidak langsung. Kata kunci: kontribusi, kemampuan koneksi, kemampuan representasi, disposisi matematis, dan prestasi belajar matematika